KONSEP AL-QUR`AN TENTANG â€ADILâ€ DALAM PERNIKAHAN POLIGAMI (SEBUAH STUDI TAFSIR DENGAN PENDEKATAN TAHLILI ) - Harahap, Ikhwanuddin (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2014)
AbstractIslam came to jahiliyah community and reformed some institutions of arabic cultures and laws. One of them was regulation of poligamy. Islam limited it in 4 (four) wives maximally, meanwhile it wasn?t limited in arabic law. The prerequest of the poligamy is ?adil. ?adil is the problematic issue in islamic thought. Some scholars say that it is impossible for husband to make ?adil between his wives, meanhile some of them say that is possible. This paper aims to show how al-quran describes the ?adil on poligamy by tahlili approach.Kata Kunci : Adil, Poligami, Tahlili